Konseptualisasi Sistem Pendidikan Akhlak Menurut Alquran dan Hadis - Anis Husni Firdaus (PSGA LP2M IAIN Pontianak, 2015)
Initially, this article describes how to reconseptualize education of akhlak based on Alquran and Hadith. Philosophically, nowadays, the concept of akhlak education is highly needed. Furthermore, it is grounded on the facts that philosophical thought remains unclear. The concepts or theories of Islamic Education are challenged by the development of human civilization which is marked by the alteration of values in societies related to the advanced technology and science. Moreover, it also explains how Alquran dan Hadith reforms the Islamic concept of akhlak education so it could offer alternative solutions and thoughts from every akhlak problems. Besides it could be a self-assessment on the weaknesses of thought.